Use of potentially inappropriate medication for elderly patients in tertiary care hospital of Riyadh, Saudi Arabia - Saleh A. Alanazi; Abdulrahman Al Amri; Mansour Almuqbil; Abdullah Alroumi; Merna Gamal Mohamed Alahmadi; Joud Obaid Ayesh Alotaibi; May Mohammed Sulaiman Alenazi; Wejdan Hassan Mossad Alahmadi; Alzahraa Hassan Saleh Al Bannay; Shorooq Khaled Ahmad Marai; Safier M. AlKhatham; Sarah Al-kanhal; et al. (Elsevier, 2024)
Background and objectives: The elderly population is affected by chronic diseases and lifelong medication. The American Geriatrics Society (AGS) Beers Criteria is a comprehensive approach to medication usage in the older population to reduce potentially inappropriate medication (PIM) use. The purpose of this study was to assess the usage of PIMs in elderly patients upon discharge from tertiary care hospital settings in Riyadh, Saudi Arabia, using the AGS Beers Criteria 2019. Methods: The data was obtained from the medical records of 1237 patients (>65 years) who were discharged from medical or surgical wards at two hospitals affiliated with King Abdulaziz Medical City. The data was analyzed to determine the prevalence of PIM prescription, and the proportional odds of the independent factors influencing outcomes were estimated using ordinal regression analysis for criteria 1 and 2, while Binary regression analysis was conducted for criterion 3. Results: There were approximately equal numbers of male and female participants in our study (male: 50.8 % vs. female: 49.2 %). One-third of the patients were above the age of 80 years, with 41 % being between the ages of 70 and 80 years. Moreover, almost 70 % of the samples had chronic illnesses. The overall prevalence of PIMs was 29.2 %, with 11 % of PIMs to be avoided in elderly patients and 17 % to be used with caution in the elderly, while disease-specific PIMs were identified in 1.2 % of the patients. The most common PIM class was proton pump inhibitors (44.41 %), and patients discharged from the surgical unit were more likely to be prescribed PIMs. Proton pump inhibitors (44.41 %) were the most inappropriately prescribed drug class, and patients discharged from the surgical unit were more likely to be prescribed PIMs. Conclusion: The study noticed that male gender, the presence of multiple diseases, and obesity are associated with more than one PIM prescription. There is a need to streamline the surgical department's prescription procedure to eliminate prescription disparities. Prescription monitoring is recommended to avoid medication errors, particularly in patients who are taking multiple medications.